Blood microvessel density, lymphatic microvessel density and lymphatic invasion in predicting melanoma metastases: systematic review and meta‐analysis. (1st January 2014) - Pastushenko, I.; Vermeulen, P.B.; Carapeto, F.J.; Van den Eynden, G.; Rutten, A.; Ara, M.; Dirix, L.Y.; Van Laere, S.
Summary: In malignant melanoma (MM) there is an urgent need to identify new markers with predictive value superior to the traditional clinical and histological parameters. Angiogenesis and lymphangiogenesis have been recognized as critical processes in tumour growth and metastasis development, and numerous studies have evaluated the significance of these parameters in predicting the prognosis in solid tumours, including MM. We set out to determine whether angiogenesis, lymphangiogenesis and lymphatic invasion (LI) are valuable prognostic markers in MM. We systematically reviewed the available literature and subsequently performed a meta‐analysis on the compiled data. To be eligible for the systematic review, a study had to provide the microvessel density (MVD), the lymphatic vessel density (LVD) or information about LI, assessed by immunohistochemistry on the primary site in patients with MM. To be evaluable for the meta‐analysis, a study also had to provide information on clinical outcome. We approached selected studies with the Reporting recommendations for tumour marker (REMARK) criteria, verifying whether they had followed the recommendations. In total, nine angiogenesis, seven lymphangiogenesis and 10 LI studies were included in our meta‐analysis, representing 419, 474 and 802 patients, respectively. Using meta‐analysis, we showed that peritumoral LVD and the presence of LI have prognostic value for patients with MM. In contrast, MVD and intratumoral LVD did not have prognostic value in these patients. LVD and LI seem to have prognostic value for patients with MM.